2022
DOI: 10.37376/1570-000-018-002
|View full text |Cite
|
Sign up to set email alerts
|

Biweekly changes in the in vitro shoot formation and growth pattern of pineapple (Ananas comosus L Merr) cv Smooth cayenne over 105 days of incubation on different hormone treatments

Abstract: BAP (6-benzylaminopurine) at 2.25 mg l-1 applied singly, in combination with indole acetic acid (IAA) at 0.175; 0.75; 1.75 mg l-1 and in combination with IAA at 1.75 mg l-1 plus gibbrellic acid (GA3) at 1.0 mg l-1 and BAP at 3.25 mg l-1 applied in combination with IAA at 1.75 and 3.75 mg l-1 were tested for their effect on the biweekly pattern of shoot formation (shoot per explant) and shoot growth (length and weight) of Smooth cayenne pineapple over 105 days of incubation. The highest shoot formation after 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Although the weight and length of the shoots used during rooting were not taken into consideration, found that heavy shoots of Spathiphyllum floribundum obtained during multiplication had a higher chance of survival during acclimatization. Hamad (2017c) found that the period of the highest increase in shoot weight and length of Smooth cayenne pineapple over each 15 days of 105 days of incubation varied depending on the hormone treatments and occurred after the shoots incubated for more than 45 days. Weight, length, and density of shoots at the beginning of the rooting stage may have great influence in its rooting response to sucrose and incubation period and proposed for future testing.…”
Section: Discussionmentioning
confidence: 96%
“…Although the weight and length of the shoots used during rooting were not taken into consideration, found that heavy shoots of Spathiphyllum floribundum obtained during multiplication had a higher chance of survival during acclimatization. Hamad (2017c) found that the period of the highest increase in shoot weight and length of Smooth cayenne pineapple over each 15 days of 105 days of incubation varied depending on the hormone treatments and occurred after the shoots incubated for more than 45 days. Weight, length, and density of shoots at the beginning of the rooting stage may have great influence in its rooting response to sucrose and incubation period and proposed for future testing.…”
Section: Discussionmentioning
confidence: 96%